Pengembangan Kurikulum Pendidikan Moral Agama pada Pendidikan Taman Kanak-Kanak - Tarsono Tarsono; Agus Salim Mansyur; Uus Ruswandi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
This study aims to identify, analyze, and develop a curriculum of religious moral education in kindergartens. The method used in this research is the R&D method (research and development) with the technique of taking data from the study of documentation, observation, questionnaires, and interviews. The results showed that: 1) the developed religious moral education curriculum was more focused on habituating positive behavior, instilling independence and discipline, and fostering faith and loyalty. These three developments applied to routine activities at school; 2) the implementation of curriculum development in religious moral education carried out in three stages, namely the preparation, development, and reporting stages; 3) the development of religious moral education curriculum has advantages, namely: the existence of a curriculum that leads to character education and self-development, the number of religious activities, professional educators, moral and religious education materials integrated with other aspects, facilities, and infrastructure that are complete and neatly arranged.